Development of hybrid and templated silicaâp123 membranes for brackish water desalination - Elma, M. (MDPI AG, 2020)
Water scarcity is still a pressing issue in many regions. The application of membrane technology through water desalination to convert brackish to potable water is a promising technology to solve this issue. This study compared the performance of templated TEOSâP123 and ES40âP123 hybrid membranes for brackish water desalination. The membranes were prepared by the solâgel method by employing tetraethyl orthosilicate (TEOS) for the carbonâtemplated silica (soft template) and ethyl silicate (ES40) for the hybrid organoâsilica. Both sols were templated by adding 35 wt. of pluronic triblock copolymer (P123) as the carbon source. The silicaâtemplated sols were dipâcoated onto alumina support (four layers) and were calcined by using the RTP (rapid thermal processing) method. The prepared membranes were tested using pervaporation set up at room temperature (~25 Â°C) using brackish water (0.3 and 1 wt.) as the feed. It was found that the hybrid membrane exhibited the highest specific surface area (6.72 m2âgâ1), pore size (3.67 nm), and pore volume (0.45 cm3âgâ1). The hybrid ES40âP123 was twice thicker (2 Î¼m) than TEOSâP123â templated membranes (1 Î¼m). Lastly, the hybrid ES40âP123 displayed highest water flux of 6.2 kgâmâ2âhâ1. Both membranes showed excellent robustness and salt rejections of >99. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.